EFEKTIVITAS KEBIJAKAN TRANSPORTASI DALAM MENGATASI PERMASALAHAN KEMACETAN DI JALAN PROTOKOL KOTA MAKASSAR - , Andi Muhammad Ahsan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Congestion has become a scourge that must be faced by almost all the major cities in the world, especially for the large cities in developing countries. With status as a major city, Makassar also experienced the same thing as the other big cities have, the congestion. A.P. Pettarani Road, Urip Sumoharjo Road, as well as Perintis Kemerdekaan Road are some of the city's main streets were hit by the congestion problem. The city government through the issuance of a policy tried to keep this problem can be overcome. Road widening policy, setting the motor-rickshaw vehicle operating areas, as well as the prohibition of on-street parking is mostly used to tackle congestion in the Makassar City. This study aimed to clarify the effect of the policy and the factors that influence the success of its implementation. This study uses a qualitative deductive method with the unit of observation is conditions of the road, while the unit of analysis is the policies that had been implemented on the road. The data collected are primary data and secondary data with the data collection techniques such as surveys, interviews, and document analysis. The variables used to assess the success of the implementation are summarized from various existing theories. Likewise with the factors that influence the policy remains inferred through a process of deduction. The study found that these policies have a successful implementation of different. Difference in the successful implementation of a policy is influenced by several factors. These factors is the lack of coordination among agencies, the number of staff or inadequate personnel, lack of funding and equipment, lack of public awareness, and the latter is the ease of access to personal vehicle ownership. In general, nothing from these policies can become an effective policy. This is because the policies only can solve the problems temporary and in the short term. There are two factors that can influence the effectiveness of the policy. These factors area consistency in the implementation also synchronize and continuity of the policies.